1981
DOI: 10.1002/cne.902030105
|View full text |Cite
|
Sign up to set email alerts
|

Developmental growth and degeneration of pulpal axons in feline primary incisors

Abstract: The life history of pulpal axons in primary mandibular incisors was examined by light and electron microscopy in 56 kittens aged from 25 days postconception to 120 days after birth. Cells resembling Schwann cells preceded the first arrival of pulpal axons, 1 week postnatally. myelination was initiated during the second week. Two months after birth the incisors were fully grown and each pulp contained about 100 axons. Between 10 and 20% of these were myelinated and ranged in size from 1 to 5 micrometer. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Thus, there is a very dynamic pattern of axonal targeting through the shift from primary (deciduous) to permanent dentition, and during the maturation of each of these sets of teeth. 62 The process of dental innervation during developmental maturation of teeth has been shown to be elegantly modulated by a cascade of molecular signals. 18 Primary afferent branches accumulate around the apical papilla, but do not enter the dental pulp proper until late in the cap stage of tooth development to finalize the branching of the primary afferents on the periphery of the pulp-dentin complex.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a very dynamic pattern of axonal targeting through the shift from primary (deciduous) to permanent dentition, and during the maturation of each of these sets of teeth. 62 The process of dental innervation during developmental maturation of teeth has been shown to be elegantly modulated by a cascade of molecular signals. 18 Primary afferent branches accumulate around the apical papilla, but do not enter the dental pulp proper until late in the cap stage of tooth development to finalize the branching of the primary afferents on the periphery of the pulp-dentin complex.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the history of prospective pulpal afferents during the interval between the establishment prenatally of permanent trigeminal ganglion cell numbers (Davies and Lumsden, 1984; Ashwell and Waite, 1991; White et al, 1995) and the onset of pulpal innervation, an event that begins postnatally concurrent with the apposition of dentin and enamel of the tooth crown (Corpron and Avery, 1973; Johnsen and Karlsson, 1977; Fried and Hildebrand, 1981a,1981b; Mohamed and Atkinson, 1983; Tsuzuki and Kitamura, 1991; Christensen et al, 1993). The ingrowth of nerve fibers into the pulp is a protracted process that, in the rat, begins several days after birth for the incisor and 1st and 2nd molars (Tsuzuki and Kitamura, 1991; Fristad et al, 1994; present study) and at about 3 weeks after birth for the late developing 3rd molar (Byers, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Fried & Hildebrand [10] used electron microscopy to describe and count the pulpal nerve supply of fully formed and resorbing feline incisors. They showed that the nerve supply varies with the age of the tooth.…”
Section: Discussionmentioning
confidence: 99%